2023
DOI: 10.3389/fpubh.2023.1226163
|View full text |Cite
|
Sign up to set email alerts
|

The costs and financing needs of delivering Kenya’s primary health care service package

Agatha Olago,
Christian Suharlim,
Salim Hussein
et al.

Abstract: IntroductionFor many Kenyans, high-quality primary health care (PHC) services remain unavailable, inaccessible, or unaffordable. To address these challenges, the Government of Kenya has committed to strengthening the country’s PHC system by introducing a comprehensive package of PHC services and promoting the efficient use of existing resources through its primary care network approach. Our study estimated the costs of delivering PHC services in public sector facilities in seven sub-counties, comparing actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Recent studies conducted in Afghanistan ( 38 ), Ethiopia ( 31 ), and Kenya ( 32 ) have similarly examined the actual and normative costs of PHC service packages. Consistent with our research, they revealed substantial resource gaps between existing PHC resources and the financial requirements to provide quality PHC services to all those who need them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies conducted in Afghanistan ( 38 ), Ethiopia ( 31 ), and Kenya ( 32 ) have similarly examined the actual and normative costs of PHC service packages. Consistent with our research, they revealed substantial resource gaps between existing PHC resources and the financial requirements to provide quality PHC services to all those who need them.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the World Health Organization’s PHC Measurement Framework and Indicators ( 30 ), key metrics that can be analyzed in the PHC-CAP Tool include inpatient and outpatient services per clinical staff, daily service output per clinical staff, cost per input, cost per service, total cost, and cost per capita—contingent on data availability. Aside from Nigeria, the PHC-CAP Tool has also been used in five additional countries, including Ethiopia ( 31 ) and Kenya ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Normative costs represent the resources needed to deliver PHC services in the health facilities in the area of interest with reasonable quality and efficiency. Normative costs (22) and Nigeria (23).…”
Section: Costing Toolmentioning
confidence: 99%